PERANAN LEMBAGA KEMASYARAKATAN DALAM PEMBANGUNAN DI KELURAHAN MAMASA KABUPATEN MAMASA - Ruth Likubua; Nur Fitra; Ahmad Saleh (MITZAL (Demokrasi, Komunikasi dan Budaya) : Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2021)
The purpose of this study was to identify and describe the role of the Village Community Empowerment Institution (LPMK) in accommodating and channeling community aspirations in development in Mamasa Village, Mamasa Regency and the role of the Village Community Empowerment Institution (LPMK) in increasing community participation in development in Mamasa Village, Mamasa Regency. The type of research used is descriptive qualitative research. The results of the study indicate that the role of LPMK in accommodating and channeling community aspirations has not been maximized. LPMK does not schedule the right time to hold a meeting with each head of the environment, so it is not effective in conveying the aspirations of each head of the environment to LPMK.